Persepsi Mahasiswa Dalam Penggunaan Teknologi Pembelajaran Bahasa Arab pada Pertemuan Tatap Muka Terbatas di Masa Pandemi COVID-19 - Ayu Desrani; Suci Ramadhanti Febriani; Rosita Ilhami (Alibbaa’: Jurnal Pendidikan Bahasa Arab, 2022)
This study aims to determine how studentâ€™s perceptions in the implementation of limited face-to-face learning (PTMT) and also the use of learning technology at STAI Al-Musdariyah Cimahi. The population and samples were taken from Arabic students at STAI Al-Musdariyah Cimahi city with a total number of 29 students. This research was qualitative research with descriptive method and the data were analyzed using data source triangulation technique. The findings of this study: 1) lectures were carried out online and offline based on the results of distributing questionnaires as many as 58.6% of students determine that the implementation of learning was carried out online & offline or blended learning, 34.5% of students preferred offline learning and as many as 6.9 % set for full online. 2) learning technology used as a means of online learning, namely WhatsApp as learning monitoring, Zoom as face-to-face learning, YouTube as a media for learning Arabic. While offline learning uses projector and language labs as learning support. Based on the results of learning Arabic, it can be seen that STAI Al-Musdariyah has implemented some of the government’s recommendations to facilitate learning by applying limited ace-to-face learning (PTMT) and learning technology